2016
DOI: 10.1186/s12885-016-2810-3
|View full text |Cite
|
Sign up to set email alerts
|

RAS testing practices and RAS mutation prevalence among patients with metastatic colorectal cancer: results from a Europe-wide survey of pathology centres

Abstract: BackgroundTreatment options for patients with metastatic colorectal cancer (mCRC) include anti-epithelial growth factor therapies, which, in Europe, are indicated in patients with RAS wild-type tumours only and require prior mutation testing of “hot-spot” codons in exons 2, 3 and 4 of KRAS and NRAS. The aim of this study was to evaluate the implementation of RAS testing methods and estimate the RAS mutation prevalence in mCRC patients.MethodsOverall, 194 pathology laboratories were invited to complete an onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 27 publications
5
24
0
Order By: Relevance
“…The frequency of the variants in the mCRC samples used in this study (Table 4 and Supplemental Table 1) is in accordance with previously reported results [4,12,[18][19][20]. KRAS exon 2 variants were most commonly identified (41%) and no NRAS exon 4 variants occurred.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The frequency of the variants in the mCRC samples used in this study (Table 4 and Supplemental Table 1) is in accordance with previously reported results [4,12,[18][19][20]. KRAS exon 2 variants were most commonly identified (41%) and no NRAS exon 4 variants occurred.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the label given by EMA to EGFR-targeted agents for patients with mCRC, one laboratory did not test all relevant codons (12,13,59,61,117,146) and did not mention this limitation in the reports. This is an improvement compared to studies performed right after the labels changed [7,12,20].…”
Section: Discussionmentioning
confidence: 76%
“…Mutations affecting exon 2 codons 12 and 13 accounted for 66% and 16%, respectively, of all KRAS mutations found, in line with published positivity rates of different types of KRAS mutations in European patients with colorectal cancer 5. As shown in Figure 1, there is a significant correlation between KRAS MAF and TNP, with a Pearson correlation coefficient of 0.3881 and a p value of 0.000072.…”
supporting
confidence: 85%
“…Risk factors for colon cancer have been shown to vary by side as well with right‐sided colon cancer being associated with female sex, increasing age, history of cancer, and insulin resistance, while left‐sided tumors have been associated with heavy smoking, alcohol abuse, and a low fiber diet . A survey of pathology centers across Europe observed that the prevalence of RAS mutations was higher in right‐sided tumors than left‐sided tumors in these centers (54.6% vs 46.4%, respectively) . Patients with right‐sided colon tumors have been shown to have worse prognosis and it has been hypothesized that genetic differences in the tumor may account for these findings .…”
Section: Introductionmentioning
confidence: 99%